Pengaruh Penggunaan Media Roller Box terhadap Kemampuan Membaca Awal pada Anak Usia 5-6 Tahun - Zahra Tsabita; Rita Kurnia; Defni Satria (Universitas Lancang Kuning, 2024)
This research is moltivated by children whol have difficulty distinguishing volwels and colnsolnants. This study aims tol improlve ability tol reading skills in children aged 5-6 years at TK Negeri Pembina 3 Pekanbaru. The type olf research used is experimlental research with a olne grolup pretest-polsttest design. The polpulatioln olf the study was children in grolup b whol were aged 5-6 years at TK Negeri Pemlbina 3 Pekanbaru, toltaling 6 classes olf 80l children. The samlpling technique was purpolsive samlpling with a toltal olf 20l children aged 5-6 years. Data colllectioln techniques using early reading ability olbservatioln sheets and LKA. The data analysis technique used is a quantitative approlach. The results olf the pretest study olbtained a percentage olf 46% and the results olf the polsttest sholwed an increase in the percentage olf 81l%. Based oln the results olf the study, it can be colncluded that there is an effect olf the use olf rolller bolx mledia oln ability tol reading skills in children aged 5-6 years at TK Negeri Pemlbina 3 Pekanbaru, which is 77.78%.